PENGARUH STRUKTUR ASET, LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL - Nastiti, Rizki Dwi; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test the factors that have influence on the capital structure. These factorsare assets structure, financial performance (represented by liquidity and profitability), company size and salesgrowth. The samples are all companies which are engaged in the field of food and beverages sector which arelisted in Indonesia Stock Exchange (IDX) in 2011-2014 periods. The sample collection technique has been doneby using purposive sampling method, and it is based on the criteria which have been determined and 17companies have been obtained as samples. This research has been carried out by performing classic assumptiontest and multiple linear regressions analysis has been done by using statistic test instrument of SPSS 20.0version. The result test shows that during the research periods from 2011 to 2014 partially the assets structureand firm size variables have positive to the capital structure, meanwhile the profitability variable has negativeinfluence to the capital structure. On the contrary, the liquidity variable and the sales growth do not have anyinfluence to the capital structure of the company.Keywords: Assets Structure, Financial Performance, Firm Size, Sales Growth, Capital Structure.